Think Hickam's Dictum not Occam's Razor in paediatric HIV - Goodyear-Smith, Felicity (BMJ Publishing Group, 2014)
A 10-year-old girl with untreated congenital HIV developed acute sepsis to which she succumbed despite emergency treatment. Her red and dilated anal region with small areas of tissue breakdown due to advanced HIV destructive disease was misinterpreted as anal assault. Suffocation was then hypothesised to be the cause of her profound hypoxia and multi-organ failure. Criminal proceedings against her adoptive uncle ensued over a 5-year period at huge legal and social cost. Following the first acquittal, appellant hearings led to re-trial at which her uncle was acquitted for the second time. A shared idée fixe (anal assault and asphyxiation) resulted in the most likely clinical diagnosis (advanced HIV infection with subsequent overwhelming sepsis) being discarded. This was a case where the principle of parsimony (Occam's Razor) led to exclusion of a diagnosis when in fact multiple diagnoses applied (Hickam's Dictum), with devastating consequences for the family.